2018
DOI: 10.1371/journal.pone.0200134
|View full text |Cite
|
Sign up to set email alerts
|

Narrative comprehension beyond language: Common brain networks activated by a movie and its script

Abstract: Narratives surround us in our everyday life in different forms. In the sensory brain areas, the processing of narratives is dependent on the media of presentation, be that in audiovisual or written form. However, little is known of the brain areas that process complex narrative content mediated by various forms. To isolate these regions, we looked for the functional networks reacting in a similar manner to the same narrative content despite different media of presentation. We collected 3-T fMRI whole brain dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…The mean FD was 0.138 mm (SD = 0.06) and there were 34.52 (SD = 74.72) timepoints above a 0.50 mm threshold on average (of 6998.20 timepoints or 0.49% of the data on average). Our mean FD compares favorably to 0.12 107 , 0.13 108 , 0.15 109 , 0.18 110 and 0.24 mm 111 in other studies with typically developing participants watching videos or movies during fMRI.…”
Section: Technical Validationsupporting
confidence: 63%
“…The mean FD was 0.138 mm (SD = 0.06) and there were 34.52 (SD = 74.72) timepoints above a 0.50 mm threshold on average (of 6998.20 timepoints or 0.49% of the data on average). Our mean FD compares favorably to 0.12 107 , 0.13 108 , 0.15 109 , 0.18 110 and 0.24 mm 111 in other studies with typically developing participants watching videos or movies during fMRI.…”
Section: Technical Validationsupporting
confidence: 63%
“…Studies with naturalistic stimuli have helped elucidate neuronal mechanisms of narrative-level comprehension, which is something that would be difficult to study with presentation of single words vs. non-words or simple sentences as is typically the case in studies with non-naturalistic stimulus/task paradigms. Studies have shown that comprehension of narrative-level information that accumulates on larger timescales depends on DMN structures ( AbdulSabur et al, 2014 ; Babajani-Feremi, 2017 ; Gordon et al, 2017 ; Nguyen et al, 2019 ; Regev et al, 2013 ; Simony et al, 2016 ; Tikka et al, 2018 ; Wilson et al, 2008 ; Xu et al, 2005 ; Yarkoni et al, 2008b ; Yeshurun et al, 2017a ). The DMN structures appear to be involved across the encoding, recall, and reconstruction of narrative events presented in a movie ( Zadbood et al, 2017 , but see Gilead et al, 2014 ), with these structures’ involvement in narrative comprehension being transferable across languages also ( Dehghani et al, 2017 ).…”
Section: Use Of Movies and Narratives In Language Studiesmentioning
confidence: 99%
“…This applies to many of the studies described in this review. Recent studies have controlled for this by showing both the film and its script and inspected commonalities across the two forms of narrative presentation (Tikka et al, 2018 ) and by obtaining behavioral self-reports on the interpretation of visual and auditory narratives to inform neuroimaging data analysis (Nguyen et al, 2019 ). These serve as excellent examples of controls that help overcome potential problems.…”
Section: Challenges In Neuroimaging Studies Of Narrative Processingmentioning
confidence: 99%